2019
DOI: 10.1038/s41598-019-45055-9
|View full text |Cite
|
Sign up to set email alerts
|

Visual impairment in aging and cognitive decline: experience in a Memory Clinic

Abstract: Visual impairment is common in people living with dementia and regular ophthalmological exams may improve their quality of life. We evaluated visual function in a cohort of elderly individuals and analyzed its association with their degree of cognitive impairment. Participants underwent neurological and neuropsychological exams, neuro-ophthalmological assessment (visual acuity, intraocular pressure, rates of past ophthalmological pathologies, use of ocular correction, treatments and surgeries) and optical cohe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
45
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 68 publications
2
45
0
2
Order By: Relevance
“…To ensure effective treatment before sample collection, a second dose of TOMA was given at 7 days before sample collection. Our studies showed that TOMA treatment significantly attenuated retinal pathological changes, suggesting that tau immunotherapy could be potentially used to prevent vision loss in patients with tauopathy and improve their life quality considering that visual impairment, such as a decline in motion blindness, depth perception, color perception and contrast sensitivity, is common in AD patients [ 45 ]. Moreover, the comparable beneficial effects of TOMA on the retina and the brain [ 9 , 10 , 22 ] suggest that similar mechanisms of neurodegeneration are operating in both organs.…”
Section: Discussionmentioning
confidence: 99%
“…To ensure effective treatment before sample collection, a second dose of TOMA was given at 7 days before sample collection. Our studies showed that TOMA treatment significantly attenuated retinal pathological changes, suggesting that tau immunotherapy could be potentially used to prevent vision loss in patients with tauopathy and improve their life quality considering that visual impairment, such as a decline in motion blindness, depth perception, color perception and contrast sensitivity, is common in AD patients [ 45 ]. Moreover, the comparable beneficial effects of TOMA on the retina and the brain [ 9 , 10 , 22 ] suggest that similar mechanisms of neurodegeneration are operating in both organs.…”
Section: Discussionmentioning
confidence: 99%
“…Visual impairment has been reported as an early symptom in some individuals diagnosed with neurodegenerative disease, including AD [11,25]. Visual deficits can include reduced acuity, visual field defects, changes in contrast sensitivity, impaired object recognition, and delayed visual processing [30]. While of interest, these observations have not pinpointed specific deficits in the visual pathway that consistently account for a reduction in visual performance.…”
Section: Introductionmentioning
confidence: 99%
“…In order to correctly interpret OCT of the retina literature results in the dementia field, it is important to have in mind that retinal thickness data obtained from different OCT devices are not readily interchangeable and it is relevant to know the average thickness and volumes obtained from the particular OCT device used in each study, which are known to be influenced by age, gender and ocular pathologies [41]. Additionally, two previous studies from our own group highlighted that OCT retinal image quality significantly differs among SCD, MCI and dementia groups and is an important predictor of OCT retinal image variability within these populations [42,43]. Still, most studies in the dementia field do not include OCT retinal image quality as a covariate in the analysis, while our data show that it would be advisable to do so.…”
Section: Discussionmentioning
confidence: 99%